Meningkatkan kemampuan pengucapan kata pada anak dengan Speech Sound Disorder - Nidia Melanita (Universitas Muhammadiyah Malang, 2023)
Speech sound disorder (SSD) is a disorder in the production of speech sounds in children. SSD can make it difficult for children to understand when speaking, interfering with verbal communication, social participation and academic achievement. The purpose of this study was to determine the effectiveness of play therapy using puzzles in improving children's word pronunciation skills with SSD. The assessment methods used are clinical interview, observation, and psychological test (WISC). As a result of this play therapy, subjects began to be able to remember and memorize letters of the alphabet correctly and began to be able to pronounce words such as